A Transdiagnostic Screening Protocol for Mental Disorders Based on Research Domain Criteria (RDOC) - Hamide Ajam Zibadi (Global Journal of Medical Research, 2024)
Research Domain of Criteria RDOC helps to explore aspects of mental disorders We designed a transdiagnostic protocol for assessing mental features based on the RDOC concept We conceptualized RDOC systems as features that are measurable in clinical research For designing this protocol we used observation clinical interview and examination for surveying the cognitive system emotion system social system regulatory system circadian rhythm and sensory motor system This protocol is a screening model for assessing indicators that RDOC has considered for the psychological dimensions The protocol helps clinical research besides clinical interview of DSM to have a comprehensive quantitative and qualitative description in order to perform personalized assessment By using this protocol we have a specific profile of features that can be used for personalized formulation